2021
DOI: 10.2166/wcc.2021.450
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of water–energy–food–climate study: current status and future prospects

Abstract: The relationship between changing climate and the three sectors of water, energy and food is increasingly drawing attention today while all of them are vital for sustainable development. This paper undertakes a bibliometric analysis of 1,959 published articles from 2010 to 2020 to provide a knowledge base of current nexus studies. Main research power, knowledge domains, evolution trends and frontier hotspots are analyzed. The main conclusions are as follows: (1) The USA, China and England contributed more in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 81 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…When comparing Web of Science, Scopus, and Google Scholar, the WOS performed the best regarding the overall coverage of the journal sample population and retrieved the most unique items (Adriaanse and Rensleigh 2013). Given the breadth and impact of the WoS, many scholars use it as a data source for bibliometric analysis, such as Qiu and Lv (2014), Si et al (2019), Zhou et al (2022), andKhaled et al (2021), who used the core collection of the WoS for data collection.…”
Section: Source Of Literature Collectionmentioning
confidence: 99%
“…When comparing Web of Science, Scopus, and Google Scholar, the WOS performed the best regarding the overall coverage of the journal sample population and retrieved the most unique items (Adriaanse and Rensleigh 2013). Given the breadth and impact of the WoS, many scholars use it as a data source for bibliometric analysis, such as Qiu and Lv (2014), Si et al (2019), Zhou et al (2022), andKhaled et al (2021), who used the core collection of the WoS for data collection.…”
Section: Source Of Literature Collectionmentioning
confidence: 99%
“…Although many themes are shared across all regions (43%), a significant percentage are shared across two regions (21%) or are regionally specific (35%). Many of these map onto the nine keyword cluster themes of Zhou et al (2022): "uncertainty"; "risk analysis"; "bioenergy"; "food-energy-water nexus"; "transport"; "integrated water resource management"; "water footprint"; "infrastructure investment" and "energy efficiency"; the five research trends underpinning the temporal evolution of the nexus identified by Lazaro et al (2022): "nexus for water management and natural resource security"; "linkages between the nexus, sustainable development goals and green economy"; "application of the nexus concept at different scales" and "climate change and urban nexus challenges"; and the four cluster themes of Bian and Liu (2021): "sustainable development and water management"; "water and food intake"; "water and food" and "environmental impact. "…”
Section: Development Geographies Of Nexus Researchmentioning
confidence: 99%
“…The FEWS nexus has also been promoted as a valuable framework for confronting pressing climate and social changes (Endo et al, 2017). As FEWS research has grown over the last decade (Wang et al, 2022;Zhou et al, 2022), the majority of research efforts have focused on technical solutions to biophysical challenges of FEWS production, conversion and use (as per Newell et al, 2019). FEWS relationships have been well studied in many complex contexts, such as the relationship between food production and water use, as well as the interdependencies between energy demand and climate change impacts on food and water resources (Kaddoura and El Khatib, 2017).…”
Section: Introductionmentioning
confidence: 99%